Skiing Trauma and Safety: 17th Volume 2009
DOI: 10.1520/stp47464s
|View full text |Cite
|
Sign up to set email alerts
|

Do Helmets Reduce Fatalities or Merely Alter the Patterns of Death?

Abstract: The use of helmets has been proposed as a means of reducing the incidence of fatality in skiing and snowboarding. This paper presents results that suggest that while helmets may be effective at preventing minor injuries, they have not been shown to reduce the overall incidence of fatality in skiing and snowboarding even though as many as 40 % of the population at risk are currently using helmets. The results indicate that the use of a helmet will indeed influence the primary cause of death, but perhaps not the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 7 publications
0
9
0
Order By: Relevance
“…The authors found that helmet use was significantly higher among those who died of a non-head-related injury than among those who died of a head injury. 33 Although wearing a helmet reduces the risk of head injury, there is concern that helmets may increase the risk of neck injury, particularly among children. Our pooled results and the individual studies showed no significant association between helmet use and increased risk of neck injury.…”
Section: Discussionmentioning
confidence: 99%
“…The authors found that helmet use was significantly higher among those who died of a non-head-related injury than among those who died of a head injury. 33 Although wearing a helmet reduces the risk of head injury, there is concern that helmets may increase the risk of neck injury, particularly among children. Our pooled results and the individual studies showed no significant association between helmet use and increased risk of neck injury.…”
Section: Discussionmentioning
confidence: 99%
“…by training -resulting in injuries) in athletes of different countries as: Poland 71% Austria 38% and Greece 37% [11,13]. Shealy, et al [34,35] concluded that the use of a helmet was associated with a reduction in the number of minor head injuries, but no such reduction was observed for the more serious forms of head trauma. Tuli, et al [28] and Young [36] dealt with the dangerous and likelihood of injury in relation to the practice of skiing.…”
Section: Discussionmentioning
confidence: 99%
“…Whether males have increased risk taking behaviour or less helmet usage is unclear. Non-helmet users were 2.3 times more likely to die from a head injury than helmet users [90].…”
Section: Effects Of Equipmentmentioning
confidence: 92%